Biomodificação do colágeno dentinário por Cross-Linkers: efeito na rigidez do colágeno e na longevidade da união resina-dentina produzida pela técnica Dry-Bonding - Bianchi, Luciana [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The aims of this study were to investigate the effect of the application of cross-linkers on (1) the stiffness of dentin collagen and (2) the resin-dentin bond degradation produced by the dry-bonding technique. To respond the first objective, forty 0.3 mm-thick dentin disks were obtained from sound premolars. After complete demineralization in 10% phosphoric acid, the discs were randomly divided into 4 groups according to the treatment (n=8): deionized water (control), 0.5 mol/L carbodiimide (EDC), 5% proanthocyanidin (PA) and 5% or 25% glutaraldehyde (GA). The discs were immersed in the solutions for 60s. Collagen stiffness was assessed indirectly based on the shrinkage after dehydration, measured in a linear variable differential transformer (LVDT). For second objective, flat dentin surfaces were produced in 64 sound pre-molars. The dentin was etched with phosphoric acid 37% for 15s, followed by treatment with the same solution described previously (n=16), except for the 25%GA. After the 60s treatment, the dentin was kept moist in half of the teeth (n=8) and dehydrated by air jets in the remaining teeth (n=8). Prime & Bond 2.1 adhesive was applied in all teeth followed by the built up of a composite block. Specimens of 0.81mm² adhesive area were obtained for the microtensile bond strength test, performed after 24h or 6 months of aging in saliva-like solution. After the mechanical test, the failure type was analyzed. Eight specimens by group were prepared for nanoleakage analysis. For both experiments, data were submitted to ANOVA and Tukey tests (p<0.05). In the absence of treatment with cross-linkers (control group), the percentage of shrinkage of the dentin matrix was 60%. Only EDC (23.9%) and glutaraldehyde 25% applied for 10 min (21.7%) were able to significantly reduce dentin shrinkage after dehydration. The highest bond strength values were found for EDC and 10% GA...(Complete abstract eletronic access below)

Os objetivos desse estudo foram investigar o efeito da aplicação de diferentes agentes promotores de ligações cruzadas (cross-linkers) sobre (1) a rigidez do colágeno dentinário e (2) sobre a degradação da união resinadentina produzida pela técnica dry-bonding. Para responder ao primeiro objetivo, 40 discos de dentina com 0,3 mm de espessura foram obtidos de pré-molares hígidos. Após completa desmineralização em ácido fosfórico 10%, os discos foram aleatoriamente divididos em 5 grupos (n=8): água deionizada (controle), carbodiimida (EDC) 0,5 mol/L, proantocianidina (PA) 5% ou glutaraldeído (GA) 5% ou 25%. Os discos permaneceram imersos nas soluções por 60s. A rigidez do colágeno foi indiretamente avaliada com base na contração após desidratação, por meio de transformador linear diferencial variável (LVDT). Para responder ao segundo objetivo, 64 pré-molares humanos hígidos foram desgastados para remoção total do terço coronário, obtendo desta forma superfícies planas de dentina. Estas foram condicionadas com ácido fosfórico a 37% por 15s, seguido do tratamento com as mesmas soluções descritas acima (n=16), exceto para o GA 25%. Após um tempo pré-determinado de tratamento, a dentina foi mantida úmida em metade dos dentes (n=8), e desidratada com jatos de ar nos dentes restantes (n=8). Em seguida, em todos os dentes, foi aplicado o adesivo Prime & Bond 2.1 e foi construído um bloco de resina. Espécimes de 0,81 mm² de área adesiva foram submetidos ao ensaio mecânico de microtração, após 24h ou 6 meses de envelhecimento em saliva artificial. Também foram analisados os tipos de fratura após o teste de microtração e oito espécimes por grupo/período de envelhecimento foram preparados para análise da nanoinfiltração. Para ambos os experimentos, os dados foram submetidos aos testes de ANOVA e Tukey (p<0,05). Na ausência de tratamento...(Resumo completo, clicar acessO letrônico abaixo)
Keywords: Dentina; Colágeno; Resistência à tração; Dentin collagen